2017
DOI: 10.1080/13813455.2017.1283527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vanillin on potassium bromate-induced neurotoxicity in adult mice: impact on behavior, oxidative stress, genes expression, inflammation and fatty acid composition

Abstract: This work suggests that vanillin mitigates KBrO-induced depression, and that this neuroprotective effect proceeds through anti-oxidant and anti-inflammatory activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…8 Recently, vanillin has been found to display a significant brain protective property through its antioxidant and anti-inflammatory activities. 9 Vanillin biological properties are mainly ascribed to its phenolic compounds, ether and aldehyde moieties. 6 It is used against oxidative damage induced by several xenobiotics like pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, vanillin has been found to display a significant brain protective property through its antioxidant and anti-inflammatory activities. 9 Vanillin biological properties are mainly ascribed to its phenolic compounds, ether and aldehyde moieties. 6 It is used against oxidative damage induced by several xenobiotics like pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, they stated that KBrO 3 induced depression‐like behaviors and caused oxidative stress. [ 30 ] Dhouibi et al [ 31 ] examined neurobehavioral changes induced by chronic exposure to KBrO 3 in rats and reported that exposure to KBrO 3 caused a reduction in SOD and CAT enzyme activity levels. In another study, where the effects of KBrO 3 administration on the brain functions and behaviors of albino mice were investigated, it was shown that KBrO 3 had severely harmful effects on the central nervous system, and for this reason, its usage should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…counteracted chemically induced brain toxicity due to exposure to such agents as ethanol, carbon tetrachloride, and potassium bromate (KBrO 3 ). [66][67][68] Compared with controls, vanillin dosing was associated with decreased lipid peroxidation, oxidative stress, and generation of inflammatory cytokines in the brain. Two studies reported that vanillin (286 mg/kg, i.p.)…”
Section: Antisickling Actionmentioning
confidence: 99%